Treatment of vascular dementia in female rats with AV-001, an Angiopoietin-1 mimetic peptide, improves cognitive function - Gao, Huanjia; Liu, Xianshuang; Venkat, Poornima; Findeis, Elizabeth; Zacharek, Alex; Powell, Brianna; Mccann, Mikkala; Kim, Harold; Zhang, Zhenggang; Chopp, Michael (Frontiers in Neuroscience, 2024)
Background: Vascular dementia (VaD) is a complex neurodegenerative disorder. We previously found that treatment of VaD in middle-aged male rats subjected to multiple microinfarction (MMI) with AV-001, a Tie2 receptor agonist, significantly improves cognitive function. Age and sex affect the development and response of VaD to therapeutic intervention. Thus, the present study investigated the therapeutic effect of AV-001 on VaD in aged female rats subjected to MMI.Methods: Female18-month-old Wistar rats were subjected to MMI by injecting either 1000 (low dose, LD-MMI) or 6000 (high dose, HD-MMI) cholesterol crystals of size 70-100 µm into the right internal carotid artery. AV-001 (1µg/Kg, i.p.) was administered once daily after MMI for 1 month, with treatment initiated 1 day after MMI. A battery of behavioral tests to examine sensorimotor and cognitive functions was performed at 21-28 days after MMI. All rats were sacrificed at 1 month after